ЧИН УЛСЫН ҮЕИЙН НЭРТ ЭРДЭМТЭН САЙШАНГАА БОЛОН ТҮҮНИЙ ХЭЛШИНЖЛЭЛИЙН ЗОХИОЛ БҮТЭЭЛИЙН ТУХАЙ - Цэцэнбаатар (Acta Mongolica, 2013)
There were many famous Mongolian scholars in the history of the Qing dynasty and they left a lot of scholarly works on humanities and natural sciences. Of those famous people, Saishangga (Sayišangγ-a, 1794-1875) was a cabinet minister as well as a civil official. In some historical documents, Saishangga’s surname was recorded as Alute (阿斋特), which should be the Mongolian surname Arulad affiliated to the Chakhar tribe. Saishangga was from the Pure Blue Banner (siluγun köke qosiγu) which was one of the Eight Mongolian Banners. He had spent a lifetime serving as a chief official of the Qing government. Saishangga’s father Jinghui was also a cabinet official of the Qing dynasty while his son Chongqi was the only Number One Scholar (斋元) in the history of the Qing dynasty. Chongqi’s daughter Buyan was married to Emperor Tongzhi together with her aunt. Hence both Saishangga and Chongqi were fathers-in-law of Emperor Tongzhi. On the other hand, Saishangga was a famous linguist of that time. His linguistic works includes “Mongγol bičig-ün čiqula-yi jiγaγsan bičig” and the Mongolian-Chinese-Manchu dictionary named “Mongγol üsüg-ün quriyaγsan bičig”. The first one is a serial works with four volumes, of which the first two were written by Saishangga’s father Jinghui and revised by Saishangga while the last two were written by Saishangga himself. These works are also small-sized dictionaries with some grammatical and orthographical explanations. Saishangga’s these linguistic works rank very high in the history of Mongolian linguistic studies.